Cone-beam computed tomography for organ motion evaluation in locally advanced rectal cancer patients - Rosa, Consuelo; Caravatta, Luciana; Di Tommaso, Monica; Fasciolo, David; Gasparini, Lucrezia; Di Guglielmo, Fiorella Cristina; Augurio, Antonietta; Vinciguerra, Annamaria; Vecchi, Claudio; Genovesi, Domenico (Radiologia medica, 2021)
Purpose Due to a reported dose–response relationship in rectal cancer radiotherapy, a greater interest in dose intensification on small boost volume arises. Considering the need of an appropriate target movements evaluation, this retrospective study aimed to use cone-beam computed tomography (CBCT) for GTV and mesorectum organ motion (OM) evaluation, in locally advanced rectal cancer (LARC) patients treated with neoadjuvant chemo-radiotherapy, in prone and supine position. Methods Thirty-two LARC patients were analyzed. GTV and mesorectum were delineated on MRI co-registrated with CT simulation. GTV and mesorectum OM was estimated on all CBCTs, performed during treatment, co-registrated with CT simulation. OM evaluation was obtained, as mean shift in left and right (L–R), postero–anterior (P–A) and cranio–caudal (Cr–C) directions. Volumes variability was calculated by DICE index. Results A total of 296 CBCTs were analyzed. Mean shifts of the GTV and mesorectum in prone position were − 0.16 cm and 0.15 cm in L–R direction, 0.28 cm and − 0.40 cm in P–A direction, and 0.14 cm and − 0.21 cm, in Cr–C direction; for supine position the mean shifts of the GTV were − 0.10 cm and 0.17 cm in R–L direction, 0.26 cm and − 0.23 cm in A–P direction, 0.09 cm and − 0.11 cm in Cr–C direction. Mean DICE index for GTV and mesorectum was 0.74 and 0.86, in prone position, and 0.78 and 0.89 in supine position, respectively. Conclusion GTV and mesorectum OM was less than 4 mm in all directions in both positions, with a 1 mm less deviation in supine position. CBCTs resulted effective for OM assessment, and it could be an appropriate method for the implementation on an intensification treatment.